Aristotle to zoos a philosophical dictionary of biology - Medawar, Peter B. 1915-1987; Medawar, Jean 1913-2005 (Harvard University Press, 1983)
Intended for browsing by educated persons such as biologists, psychologists, sociologists, and other "reflective people who see in biology the science most relevant to the understanding and melioration of the human condition." Lengthy enties. Index.
Keywords: Biologie - Dictionnaires anglais; Biology -- Dictionaries; Biology -- Dictionary -- English; Biologie; Englisch; Wörterbuch